Trochlear nerve palsy associated with claude bernard-horner syndrome after brainstem stroke - Bazan, Rodrigo [UNESP]; Braga, Gabriel Pereira [UNESP]; Gomes, Daniela Laranja [UNESP]; Yamashita, Seizo [UNESP]; Betting, Luiz Eduardo Gomes Garcia [UNESP]; Resende, Luiz Antonio de Lima [UNESP] (Karger Publishers, 2011)
The association of unilateral trochlear nerve palsy with Claude Bernard-Horner syndrome represents a rare clinical condition. We present the case of a patient with this unusual presentation. The investigation performed implicated cerebrovascular disease as the underlying cause of the condition in this patient. © 2011 S. Karger AG, Basel.
Keywords: Claude Bernard-Horner syndrome; Ocular palsy; Stroke; Trochlear nerve; nitroprusside sodium; adult; blood pressure; brain stem; case report; Caucasian; cerebellum; cerebrovascular disease; Claude Bernard Horner Syndrome; clinical examination; consciousness; contrast enhancement; diplopia; disease association; dysarthria; female; headache; hemiparesis; Horner syndrome; human; hypertension; mesencephalon; neurologic examination; nuclear magnetic resonance imaging; pons; priority journal; remission; trochlear nerve palsy